Developing an historical gaze: a comparative study of pre-service social science teachers with differential backgrounds in school history - Glanvill, Kathleen Siobhan (My University, 2014)
This research report investigates the opportunities and challenges pre-service social science educators with differential backgrounds in school history confront when developing both substantive and procedural historical knowledge for history teaching. It is particularly concerned to understand how differential backgrounds in school history affect the acquisition of an historical gaze. The report employs qualitative methods such as interviews and focus groups with nine pre-service educators who have diverse experiences of school history to ascertain whether choosing history as a matric subject enhances the development of an historical gaze or not. It also analyses evidence from two written examinations in order to investigate whether these pre-service educators are not only able to recognise but are also able to realise historical thinking concepts, as defined by the Canadian Historical Thinking Project, that imply sophisticated acquisition of an historical gaze. At the moment the data suggests that the students’ differential backgrounds in school history have not affected the acquisition of an historical gaze. There do not seem to be substantive differences except where students were exposed to school history that was taught as both substantive and procedural knowledge with opportunities to engage in the process of historical inquiry.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Education Johannesburg, 2014